Newton’s disc in Ganot’s Traité de physique and the discourse of the mechanical objectivity. The diffusion of a demonstrative pattern between 1900 and 1936 in secondary and university education - Guijarro Mora, Víctor; González de la Lastra, Leonor (CIAN-Revista de Historia de las Universidades, 2023)
“Newton’s disc” was transformed by Adolphe Ganot’s Traité élémentaire de physique, first published in 1851, into the standard and complete demonstration of the recomposition of white light. This artífice closed the argumentative circle that had be gun with the prism experiment regarding its decomposition. But the results were not conclusive: greyish tones were seen where the white ones were expected, and a question was raised regularly: was the final result a consequence of the colors mixing themselves or of our sensations? In this study, taking into account the different elements that make up the demonstration (the textual, the iconographic, and particularly, the material) the authors reconstruct the narrative that kept the verification away from personal and subjective interpretations. In this way, a convincing discourse was obtained due to its simplicity and reproducibility, which was replicated in the first third of the 20th century in Spanish secondary and university education centres despite the fact that it didn’t have a consistent probative value.
Keywords: Newton disc; Adolphe Ganot; secondary education; university education; educational instruments; mechanical objectivity and subjectivity